THE ROLE OF ETHNOMATHEMATICS IN MATHEMATICS EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Agung Tralisno; Syamiah Alfi (As-Sulthan Journal of Education, 2026)
This study examines the role of ethnomathematics in mathematics education through a systematic literature review. The scope of the study includes an analysis of various research findings related to the integration of cultural elements in mathematics learning. The objective of this study is to identify the contributions of ethnomathematics to students’ conceptual understanding, numeracy literacy, problem-solving skills, as well as their affective and cultural development. The method employed is a literature-based study involving the review of relevant scholarly articles. The findings indicate that ethnomathematics is effective in enhancing conceptual understanding by connecting abstract mathematical ideas to cultural contexts that are familiar to students. In addition, this approach supports the development of numeracy literacy and problem-solving abilities, while also increasing students’ motivation and engagement in learning. Ethnomathematics further contributes to fostering cultural awareness and strengthening students’ cultural identity. However, its implementation still faces challenges, particularly in terms of teacher readiness and the limited availability of culturally integrated learning materials. In conclusion, ethnomathematics is a comprehensive instructional approach with strong potential to improve mathematics learning outcomes across cognitive, affective, and social domains.